PHARMACOECONOMIC EVALUATION OF RUFINAMIDE USE FOR THE LENNOX-GASTAUT SYNDROME TREATMENT - N. K. Mazina (Фармакоэкономика, 2016)
Among epileptic encephalopathies, the Lennox–Gastaut syndrome is considered to be one of the most severe. It is a childhood-onset disease that leads to early disability and mental retardation and is associated with significant costs of medical care and patient nursing. In the Russian Federation, the supposed number of patients with the Lennox–Gastaut syndrome is between 1400 and 9240 people. Rufinamide is one of the most powerful agents being used for the adjuvant therapy of this syndrome. In order to evaluate the efficacy of the drug in this pathology, a systematic review of publications of the results of the respective clinical studies was performed. Eleven articles were selected for generation of pooled groups and meta-analysis. Rufinamide used as an adjunctive therapy has been shown to substantially increase the chances of successful result (HR=3.1 [2.0; 4.9], p=0.000). Pharmacoeconomic modelling (a decision tree type) allowed revealing that the use of rufinamide adjunctive therapy for the Lennox–Gastaut syndrome reduces total costs of treatment and nursing of these patients with minimum effect on the budget.